PENCEGAHAN KEGAGALAN IMPLAN DENTAL YANG DISEBABKAN PERI- IMPLANTITIS DENGAN PENGGUNAAN CONCENTRATED GROWTH FACTOR - Maitimu, Fergy Christin; Suwandi, Trijani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: The destruction that occurs in peri-implantitis, if left untreated, can eventually lead to dental implant failure. Autogenous growth factor is prepared by centrifugation of whole blood samples and has been widely applied in wound healing and tissue regeneration. This platelet concentrate can be used alone or in combination with other biomaterials for soft tissue healing or bone formation. CGF (concentrated growth factor) is a derivative of PRF (platelet-rich fibrin) and has the same 3-dimensional structural complex as PRF. However, it contains more growth factors than PRF and has a more rigid fibrinogen structure. Aims: The objective of this systematic review is to obtain scientific data related to the use of concentrated growth factors in peri-implantitis treatment in order to avoid dental implant failure. Method: A total of 5,339 studies were initially identified from the three databases (Wiley, Researchgate and Google Scholar) between January 2018 and July 2023. Result: Three randomised clinical trials (RCTs) were selected for analysis. Conclusion: Concentrated Growth Factor (CGF) can be employed in combination with bone graft material for the treatment of peri-implantitis, with the objective to prevent dental implant failure that may result from peri-implantitis. However, it is not the sole recommended approach.